Cutaneous Candidiasis in a Gottingen Minipig: A Potential Pitfall in Preclinical Studies. (December 2017) - Ramot, Yuval; Obaya, Ana; McNamara, Alice; Nyska, Abraham
The Göttingen minipig is often used in preclinical toxicity studies. Therefore, knowledge of spontaneously occurring pathologies is important to differentiate them from test drug–related effects. We report on a Göttingen minipig, which developed exudating widespread dermatitis during a preclinical toxicity study with a subcutaneously injected drug. The lesions were resistant to topical and oral antibacterial medications. Skin cultures were positive for Candida albicans, and treatment was changed to topical antifungal cream with quick resolution of the skin lesions. Cutaneous candidiasis in pigs has been rarely reported in the literature, and this is the first report on such condition in preclinical toxicity studies. Knowledge of this condition, which is not drug related, is important, especially in toxicity studies involving subcutaneous injections that are commonly accompanied by inflammatory skin reactions.